Analisis Informasi Citra Anatomi Pemeriksaan MRI Shoulder Joint antara Posisi Pasien Netral dan “Abduction and External Rotation” Menggunakan Sekuen Gradient Echo T2* - Rini Indrati; Siti Masrochah; Made Nia Cahya Dewi (Poltekkes Kemenkes Semarang, 2017)
Background : Has conducted a study of differences in anatomical image information on sequences Gradient Echo T2* to the neutral position and the Abduction and External Rotation in Radiology Panti Rapih Yogyakarta Hospital. Abduction and External Rotation positions are positions that obtained when the patient is in the supine position with the hands under the head, resulting in external rotation and abduction of the humerus. This position is useful to show the subtle picture of the infraspinatus tendon and anterior labrum is normal and can detect abnormalities of the rotator cuff. The neutral position is a position that is obtained when the patient supine with the shoulder and arm parallel to the body with a neutral or slightly towards the external rotation. The purpose of this study is to determine the difference and which one is a better position to produce anatomical image information between sequences Gradient Echo T2* with a neutral position and Abduction and External Rotation MRI of shoulder joint.Methods : This research is a quantitative research with experimental approach. The study was conducted at Radiology Installation Panti Rapih Yogyakarta Hospital, the data in the form of 10 image sequences Gradient Echo T2* use a neutral position and 10 image sequences Gradient Echo T2* use position Abduction and External Rotation MRI of shoulder joint of 10 volunteers. Ratings are subjective images of the two respondents include the glenoid labrum, rotator cuff, joint space, border line and fluid in accordance with the level of clarity. Analysis of the data from the second respondent in kappa test (Realibility inter observer) to determine the level of common perception (measure of agreement) of the respondents after the data is selected from one of the respondents and the wilcoxon test for the presence or no difference between the two positions.Result : Results wilcoxon test in this study expressed a significant difference between the neutral position and the position of Abduction and External Rotation in total one image (the value of ρ 0.001), and percriteria namely the glenoid labrum (value ρ: 0,025), rotator cuff (the value of ρ: 0,008 ), joint space (value ρ: 0,025), borderline (value ρ: 0,005), and fluid (value ρ: 0,014), of the value of ρ total of one image with a value of ρ percriteria can be concluded that the sequences Gradient Echo T2 * use position Abduction and External Rotation can generate image information of shoulder joint anatomical MRI better than on sequences Gradient Echo T2* use a neutral position.Conclusion : There was a significant difference in the overall image information between the Gradient Echo T2* sequences using neutral position and Abduction and External Rotation position in total image with a p-value of 0.001 (p0.05).